Análise da variabilidade climática, demandas hídricas e mudanças Climáticas: o hidrossistema Jaguaribe-Metropolitano, Ceará, Brasil - Silva, Greicy Kelly da (2024)
Water is essential for life on Earth, but increasing demand due to population growth and economic development has increasingly pressured the water resources sector. Climate and economic changes influence water availability and demand, creating uncertainties for the future. In the State of Ceara, rainfall variability, intermittent rivers, and high evaporation rates increase uncertainties and complexity in water management. That said, the objective of this study was to assess the impacts of climatic phenomena and anthropogenic actions, along with greenhouse gas emissions, on the Jaguaribe-Metropolitano System (JMS). Among the main methodologies employed in this study are descriptive statistics analysis, seasonal, interannual, and decadal variabilities, Standardized Precipitation and Runoff Indices for precipitation and flow series; the evaluation of future water demand behavior in scenarios of population, industrial, and irrigation growth using an exponential growth model; the assessment of precipitation, flow, and temperature variation patterns using data from the Coupled Model Intercomparison Project Phase 6 (CMIP6) models compared to observed data from the Global Precipitation Climatology Centre and Climatic Research Unit. Additionally, analyses of projections and their possible impacts associated with climate change were considered, considering scenarios SSP2-4.5 and SSP5-8.5; the evaluation of the impact of climate change on water availability in the JMS using a Water Allocation Management Information System (SIGA) based on CMIP6 model data, considering present and future periods for the aforementioned scenarios. In the analyses mentioned above, it was found that extreme drought and rainfall events are already a reality and may become more frequent in the coming decades. Additionally, analyzing the phases of Pacific and Atlantic Ocean climate oscillations revealed their influence, along with sea surface temperature, on precipitation patterns in the state of Ceara. Examining ETS model projections for water demand in different scenarios revealed significant similarities in results in some sectors and basins. Projections also indicated a continuous increase in consumptive demand over time for some areas. Climate change will have significant implications in the last three decades of the 21st century, especially under high greenhouse gas emission scenarios, necessitating mitigation efforts. The SIGA model stood out with a solid performance in simulating monthly volumes of the water system. Variations in reservoir levels over decades were observed, with periods of scarcity interspersed with availability, raising concerns about water supply. CMIP6 models revealed significant variations in reservoir storage, highlighting the sensitivity of some models to different scenarios. Simulations under future scenarios SSP2-4.5 and SSP5-8.5 indicated significant variations in storage volumes and demand fulfillment, emphasizing the importance of considering multiple factors in water resources management.